Relativistic and QED corrections for the ground state lithiumlike ionization energies. (16th December 2021) - Earwood, William P; Davis, Steven R
Abstract: The ground state ionization energies of Z ⩽ 10 lithiumlike ions are calculated using fully correlated Gaussian wavefunctions. Leading-order relativistic corrections are evaluated, while QED corrections are established with small uncertainties by directly calculating the Araki–Sucher energy and expanding the three-electron Bethe logarithm in 1/ Z . The non-relativistic α 6 level shifts have also been calculated, and we have used these energies to recommend ionization energies, which include estimates of the influence of the relativistic portion of the α 6 energy. The results emphasize the importance of the direct computation of the complete α 6 correction, but also the need for new, higher accuracy experimental ionization limits.